PERBANDINGAN BIAYA DAN STRATEGI PEMBIBITAN DUA PENGUSAHA PEMBIBITAN KELAPA SAWIT DI KABUPATEN BANYUASIN PROVINSI SUMATERA SELATAN - Juniarrafiq, Mhd. Dwika; Lubis, Yusniar; Siregar, Tumpal HS; Manullang, Endang Sari (AGRIBIOS, 2025)
The use of superior seeds in the community is still very limited, among other things, due to the low knowledge of farmers about superior seeds and the very low ability of farmers to buy seeds because of the very high prices. in meeting the certified palm oil seed market it is necessary to use cost analysis and strategies in developing certified palm oil seeds to farmers in increasing oil palm production and increasing farmers' income in utilising the land area owned. The purpose of this study is to determine the comparison of the cost analysis of the procurement of certified oil palm seeds CV. Gotama and CV. BSM and development strategies carried out in the procurement of certified oil palm seeds. Research Methods This research uses primary data approaches and secondary data. sample withdrawal in this study is the census method or other names, namely the type of Non Probability Sampling, namely CV. Gotama and CV. Bumi Sriwijaya Mandiri with cost and strategy analysis methods. The results showed that the revenue generated at CV. Gotama worth Rp. 8,220,634,998 and at CV. BSM worth Rp. 7,589,670,856. This means that the income generated by CV. Gotama in value is greater than CV.BSM but with the total production produced CV.BSM can streamline production and production prices and swot analysis, namely Quadrant I. Which means the company has an advantageous situation. Cv Gotama and Cv Bumi Sriwajaya Mandiri have opportunities and strengths so that they can take advantage of existing opportunities.